Harley Quinn. Vol 2, Friends with detriments - Kalan, Elliott, 1981- (DC Comics, 2026)
Harley Quinn's latest misadventures continue in the next thrilling volume from acclaimed writer Elliott Kalan! Whether she's dodging assassins, joining the neighborhood party planning committee, or dealing with an identity crisis only she could have, Gotham's most unpredictable antihero is in for a chaotic ride. Featuring the debut of the soon-to-be-infamous Gunbuddies, this collection is packed with action, humor, and classic Harley mayhem.